Representasi Identitas Perempuan Arab Saudi dalam Film Naga Karya Meshal Al-Jasser: Analisis Semiotika Roland Barthes - Siti Hani Zakiyah; Rohanda Rohanda; Muhammad Abdul Halim (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2026)
This study identifies the representation of female identity in the film Naga (2023) by Meshal Al-Jasser using Roland Barthes' semiotic theory, which focuses on denotative, connotative, and myth meanings. The research method used is qualitative descriptive with observation-note data collection techniques. Data were obtained through observations of dialogues and visual symbols that represent female identity conflicts in the film Naga. The research results on 12 findings show that visual symbols such as the view through the carpet hole function as connotative signs of the limitation of the main character's mobility. This symbol represents the myth of patriarchal father roles as authority holders who become obstacles to women's individual freedom in the narrative of the film Naga. The film Naga voices satirical criticism concerning women related to fair and humane social rights. This study concludes that the film Naga becomes a medium of social representation that depicts women's struggle in balancing between tradition and modernity.